The star shard - 585498 Durbin, Frederic S author (Boston : Houghton Mifflin, 2012)
A twelve-year-old slave on a gigantic, traveling "wagon city" joins forces with a new--and magical--slave, and as they plan their escape they encounter mystery, enchantment, and deadly monsters while their one chance for freedom draws ever nearer.